Pencabutan Permohonan Eksekusi Hak Tanggungan dalam Penyelesaian Sengketa Ekonomi Syariah (Studi Perkara Nomor 5/Pdt.Eks/2023/PA.Sdn) Ditinjau dari Teori Maslahah Mursalah - Sela Saras Wati; Aziza Aziz Rahmaningsih (Fakultas Syariah IAIN Kerinci, 2026)
This study aims to analyze the factors underlying the revocation of a Mortgage Right execution request after the execution seizure stage in sharia economic disputes and examine this practice from the perspective of maslahah mursalah in Case Number 5/Pdt.Eks/2023/PA.Sdn at the Sukadana Religious Court. This study uses a qualitative method with an empirical juridical approach. Primary data were obtained from case file Number 5/Pdt.Eks/2023/PA.Sdn and the results of interviews with judges, clerks, and bailiffs at the Sukadana Religious Court. Secondary data were obtained through a literature review of relevant laws and regulations, legal literature, and previous research. Data analysis was conducted using the Miles and Huberman interactive analysis model through the stages of data reduction, data presentation, and drawing conclusions. The results of the study indicate that the revocation of a Mortgage Right execution request is influenced by interrelated legal, procedural, social, and economic factors. From a legal aspect, revocation is possible because there is no prohibition on revocation before the auction stage and it is based on a written peace agreement between the parties. From a procedural perspective, all stages of the execution have been carried out in accordance with legal provisions up to the execution seizure stage. From a social and economic perspective, revocation was chosen because it provides a more effective resolution space, reduces the potential for conflict, and is more efficient in terms of cost and time. From a maslahah mursalah perspective, this practice reflects an effort to realize the public interest through protecting creditors' rights, preventing greater losses, and resolving disputes more proportionally. The novelty of this research lies in the analysis of the phenomenon of revocation of Mortgage Right execution requests after the execution seizure stage in sharia economic disputes through an empirical juridical approach and a maslahah mursalah perspective. Unlike previous research that generally focuses on the execution procedures and their obstacles, this study highlights the factors underlying the revocation of execution and its integration with the principle of public interest in religious court practice